2019
DOI: 10.3390/ijms20184626
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of CYP2C8 Alter First-Electron Transfer Kinetics and Increase Catalytic Uncoupling

Abstract: Cytochrome P450 2C8 (CYP2C8) epoxygenase is responsible for the metabolism of over 60 clinically relevant drugs, notably the anticancer drug Taxol (paclitaxel, PAC). Specifically, there are naturally occurring polymorphisms, CYP2C8*2 and CYP2C8*3, that display altered PAC hydroxylation rates despite these mutations not being located in the active site. Herein, we demonstrate that these polymorphisms result in a greater uncoupling of PAC metabolism by increasing the amount of hydrogen peroxide formed per PAC tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…We propose that L375 is important for stabilizing a nearby α‐helix which carries the crucial residues for the electron shuffling process, and that the L375V mutation destabilizes the helix‐mediating electron shuffling, thereby disrupting the catalytic function of CYP4F3. Point mutations affecting electron transfer in CYP enzymes have been reported before, such as polymorphisms in CYP2C8 affecting its hydroxylase function 40 . The same goes for variations in electron transfer partners that disrupt CYP activity 41 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We propose that L375 is important for stabilizing a nearby α‐helix which carries the crucial residues for the electron shuffling process, and that the L375V mutation destabilizes the helix‐mediating electron shuffling, thereby disrupting the catalytic function of CYP4F3. Point mutations affecting electron transfer in CYP enzymes have been reported before, such as polymorphisms in CYP2C8 affecting its hydroxylase function 40 . The same goes for variations in electron transfer partners that disrupt CYP activity 41 …”
Section: Discussionmentioning
confidence: 93%
“…Point mutations affecting electron transfer in CYP enzymes have been reported before, such as polymorphisms in CYP2C8 affecting its hydroxylase function. 40 The same goes for variations in electron transfer partners that disrupt CYP activity. 41 …”
Section: Discussionmentioning
confidence: 98%
“…Being capable of producing reactive oxygen species, cytochrome enzymes may contribute to the cellular oxidation–reduction balance through a process in their reaction cycle called uncoupling 15 . Uncoupling describes the formation of ROS by decomposition of reaction intermediates instead of completing substrate oxidation 5 . It is suggested that uncoupling can have damaging effects by contributing to the cellular ROS levels 16 .…”
Section: Discussionmentioning
confidence: 99%
“…15 Uncoupling describes the formation of ROS by decomposition of reaction intermediates instead of completing substrate oxidation. 5 It is suggested that uncoupling can have damaging effects by contributing to the cellular ROS levels. 16 We measured H 2 O 2 generation by isolated CYP2C8 enzymes and detected an increased formation in the CYP2C8*3 variant enzyme enhanced by zoledronic acid and also by arachidonic acid (Figure 4C,F).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation